2021
DOI: 10.1007/s00300-020-02780-6
|View full text |Cite
|
Sign up to set email alerts
|

Variation among colonies in breeding success and population trajectories of wandering albatrosses Diomedea exulans at South Georgia

Abstract: The wandering albatross, Diomedea exulans, is a globally threatened species breeding at a number of sites within the Southern Ocean. Across the South Georgia archipelago, there are differences in population trends even at closely located colonies. Between 1999 and 2018 the largest colony, at Bird Island, declined at 3.01% per annum, while in the Bay of Isles, the decline was 1.44% per annum. Using mean demographic rates from a 31-year study at Bird Island and an 11-year study of breeding success at Prion Islan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
(41 reference statements)
1
6
0
Order By: Relevance
“…The population decreases of other albatrosses in the Southern Ocean are assumed to be caused by the impacts of fisheries and climate change (Cleeland et al, 2021; Pardo et al, 2017; Rackete et al, 2021), and are similar in scale to the population decrease we found for Tristan albatrosses. Our results suggest, however, that it is mostly the effect of invasive mice on breeding success that is causing the decrease of Tristan albatrosses, and that the population could likely recover once this threat has been removed.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The population decreases of other albatrosses in the Southern Ocean are assumed to be caused by the impacts of fisheries and climate change (Cleeland et al, 2021; Pardo et al, 2017; Rackete et al, 2021), and are similar in scale to the population decrease we found for Tristan albatrosses. Our results suggest, however, that it is mostly the effect of invasive mice on breeding success that is causing the decrease of Tristan albatrosses, and that the population could likely recover once this threat has been removed.…”
Section: Discussionsupporting
confidence: 78%
“…Young albatrosses are more vulnerable to bycatch in fisheries than are adults (Gianuca et al 2017;Frankish et al 2021) Several albatross populations on predator-free islands in South Georgia are declining (Pardo et al 2017;Rackete et al 2021), whereas Black-browed Albatrosses (Thalassarche melanophris) breeding in the Falkland Islands/Malvinas are increasing (Ventura et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having survived to this age and appearing healthy during the ground survey a month earlier, and with no evidence of carcasses seen in the aerial imagery, it is unlikely that the chicks had died, so either they were overlooked, or they had fledged earlier than expected. Differences in the breeding biology of wandering albatross at Bird Island and in the Bay of Isles has been noted previously, so further detailed study of this site is warranted (Rackete et al, 2021). The surveys were conducted later in the season than originally planned, with the first attempt a month earlier being postponed due to high winds and poor visibility.…”
Section: Discussionmentioning
confidence: 97%
“…The seven smaller islands are infrequently surveyed due to their inaccessibility and their lesser importance as nesting sites, however, they still make up approximately 20% of the population within the Bay of Isles. The most recent surveys conducted in 2003/2004 and 2014/2015 show a decrease in the population across all of the islands (Poncet et al, 2006(Poncet et al, , 2017, but the decline in the Bay of Isles is smaller than elsewhere at South Georgia (Rackete et al, 2021).…”
Section: Case Study -Wandering Albatross -Bay Of Islesmentioning
confidence: 93%